Adherence to guidelines of diagnostic and therapeutic practices for suspected infections of cardiac implantable electronic devices. (14th October 2021) - De Ciancio, G; Filippetti, L; Blangy, H; Huttin, O; Goehringer, F; Juilliere, Y; Sadoul, N; Selton-Suty, C
Abstract: Background: Despite guidelines describing the optimal diagnostic and therapeutic procedures of patients with suspected infection of cardiac implantable electronic device (CIED), the management of such patients is often challenging. Purpose: The aim of this study was to describe our diagnostic and therapeutic practices for suspected CIED infection and to compare them to European Heart Rhythm Association (EHRA) guidelines. Methods: Patients hospitalized in our tertiary care hospital for suspected CIED infection from 2014 to 2019 were retrospectively included. We applied the EHRA classification and compared diagnostic and therapeutic management to EHRA guidelines. Results: Among 184 patients (mean age 72.3±12.4 years), 137 had a proven infection of the lead (either by TTE/TEE, by [18F]FDG PET/CT, or by positive culture of the lead) or an isolated pocket infection without proof of lead infection and 47 had no proof of infection of CIED. According to EHRA classification, CIED infection was considered as definite in 145 patients, possible in 31 and excluded in 8. Regarding recommended diagnostic procedures, blood cultures were performed in 90.8%, TTE in 97.8%, TEE in 85.9%, [18F]FDG PET/CT in 50.5% and imaging for embolisms in 78.3% of the patients. Compared to therapeutic recommendations for the 145 cases of definite CIED infection, device removal was performed in 96 patients (66.2%), antibiotic therapy was prescribed in 130 (89.7%), with a duration equal or superior to the one recommended in 105 (72.4%) of the patients. One-year survival rate was 66.3% and was better in patients with device removal than in patients without, both in the whole population (respectively 77.7% and 48.6%) and in the patients with definite CIED infection (80.0% vs 49.0%). After adjustement on age and Charlson's score, patients without device removal had a significantly higher risk of 1-year mortality (HR=3.40 [1.84–6.26], p=0.0001). Conclusion: Suspicion of CIED infection are difficult situations. The use of theoretical classification helps to define the different types of cases and the resultant therapeutic approach. In daily practice, our study shows that the strict adherence to these guidelines is not always possible. This study shows a relatively good use of diagnostic procedures. However, theoretical advice for medical therapy and removal procedures are not always properly followed. To improve patients' prognosis, infected device removal must be systematically discussed in multidisciplinary endocarditis team, weighing the benefit-risk ratio of the strict appliance of the guidelines. Funding Acknowledgement: Type of funding sources: None.